APLIKASI KEBIJAKAN HUKUM PIDANA TERHADAP PELAKSANAAN REHABILITASI PECANDU DALAM TINDAK PIDANA NARKOTIKA (STUDI DI REHABILITASI KEMENTERIAN SOSIAL PAMARDI PUTRA “INSYAF” SUMATERA UTARA) - Arie Kartika; Madiasa Ablisar; Marlina Marlina; Edy Ikhsan (Universitas Sumatera Utara, 2015)
ABSTRACT Law enforcement in narcotics which uses criminal instrument is not the only prioritized policy; the strategies of law enforcement in narcotics such as treatment strategy and rehabilitation strategy are also needed. One of the examples of social rehabilitation centers in North Sumatera is PSPP (Social Rehabilitation Center Pamardi Putra) ‘Insyaf’ of North Sumatera, under the aegis of the Social Ministry of the Republic of Indonesia. It is responsible for carrying out the mandate in the policy of criminal law on the implementation of rehabilitation for drug addicts. The policy of handling (criminal political) crimes was done by using “penal” (criminal law) and non-penal (outside criminal law) facilities. Therefore, penal policy is related to the functionalization in some stages: formulation, application, and execution. The application of the policy in criminal law in implementing rehabilitation for drug addicts is synchronized between written policy planning and service planning for drug addicts. The implementation of social rehabilitation gives legal benefit to drug addicts. Keywords : criminal politicy, criminal law, social rehabilitation, drug addicts